Visions of public safety, justice, and healing: the making of the rape kit backlog in the united states - Quinlan, Andrea (Social and Legal Studies)
Large backlogs of untested sexual assault kits have recently come to light in cities across the United States, fueling public controversies over criminal justice responses to sexual assault and sexual assault forensic services. This article examines these controversies to reveal how kit backlogs have come to matter as a political problem. Using a range of textual data, this article traces the history of the sexual assault kit backlog in New York City and contemporary national campaigns around kit backlogs to examine how sexual assault kit backlogs are being defined as threats to public safety, justice, and healing for victims of crime. Drawing on theoretical insights from actor-network theory, institutional ethnography, and feminist technoscience studies, this article examines the implications of the current framing of kit backlogs for sexual assault survivors and their allies, and current dialogues about criminal justice responses to sexual assault.- Reproduced
Keywords: Actor-network theory, Feminist technoscience studies, Institutional ethnography, Rape kit backlogs, Sexual assault forensics